A specific rod model based efficient analysis and design of hanger installation for self-anchored suspension bridges with 3D curved cables. (1st March 2016) - Sun, Yuan; Zhu, Hong-Ping; Xu, Dong
Highlights: Specific rod model to simulate the main framework deformations of bridge. Efficient algorithm to identify the mainly concerned parameters of construction step. Unstrained length based searching algorithm for hanger installation design. Abstract: Hanger installation is important in constructing self-anchored suspension bridges. The installation plan is obtained from comparative studies of concerned information in tentative construction steps. The comparisons are generally performed manually using detailed nonlinear finite element method (NFEM), particularly for those with 3D curved cables. However, the procedure is complex and time consuming. Thus, this study proposes an efficient method to analyze mainly concerned parameters of hanger installation plan, through which automatically optimized strategy of updating ideal construction steps is developed to yield the plan totally by linear coordinate iteration. To realize it, an indiscrimination coordinate rod model (ICRM) combined with coordinate iteration-based methods (CIMs) is proposed for the modeling of the construction steps. The ICRM simulates the major deformation system of the total bridge with specific rods, and then the CIMs identify its equilibrium by linear algorithms to solve the coordinates directly. On the basis, NFEM can be avoided and the design efficiency is greatly improved for the plan. The effectiveness of the proposed method is demonstrated by comparison case studies, field test verification and application discussion in a real-scale bridge.